From the Old, the Best: Parathyroidectomy in the Management of Soft-Tissue and Vascular Calcification in Patients with Chronic Renal Disease - P. Mariel Hernandez; B. Daniel Enos; T. Gonzalo Labarca; A. Guillermo Vanderstelt (Case Reports in Nephrology)
Introduction. Bone mineral disease in patients with chronic kidney disease (CKD-MBD) is a clinical syndrome involving bone, biochemical changes, and extraosseous calcification. These complications increase morbidity and mortality. Prevalence reports are rare. Case Report. This case shows a young woman on peritoneal dialysis (PD) for 10 years with severe secondary hyperparathyroidism and soft-tissue calcifications in the hands, pelvis, and right knee, as well as severe vascular calcification, managed with calcimimetics without success. We decided to perform subtotal parathyroidectomy (STPTX). Three months after surgery, she had satisfactory evolution, despite notable hungry bone disease, without bone pain or functional limitation and almost no calcifications. Discussion. The benefit of hemodialysis has been shown with better volume management and improvement of calcium/phosphate products. STPTX allowed biochemical control and calcification improvement, with an evident better quality of life for our patient. Therapeutic alternatives need to be tailored to the patient’s characteristics in the calcimimetics era.